Factors Associated with the Severity of COVID-19 at H. Adam Malik Hospital, Medan, Indonesia - Destylya, Dyana; Bintang Yinke Magdalena Sinaga; Siagian, Parluhutan; Eyanoer, Putri Chairani (TALENTA Publisher, Universitas Sumatera Utara, 2023)
Background: Several studies have shown an association among laboratory values, comorbidities, and the severity of COVID-19. This study aimed to find the factors associated with the severity of COVID-19 patients in Adam Malik Hospital. Method: This is a descriptive study with a cross-sectional design. The subjects were COVID-19 patients from December 2020 to April 2021 whose data were in the form of secondary data obtained from their medical records. The inclusion criteria were patients diagnosed with COVID-19 based on RT-PCR while the exclusion criteria were incomplete medical record data. Statistical analysis was conducted via the following tests Kruskal Wallis Test, Kolmogorov Test, and Chi-Square based on the data category. Results: A total of 110 subjects were enrolled in this study. Most subjects were male (55.45%) with age >40 years old (66.36%). The laboratory values of lymphocyte count, NLR, D-dimer, procalcitonin, ferritin, fibrinogen, and CRP were significantly associated with the severity of COVID-19. Also, there were several comorbidities statistically associated with the severity of COVID-19, including hypertension, diabetes mellitus, coronary artery disease, renal disease, and HIV (p <0.05). Conclusion: Lymphocyte count, NLR, CRP, procalcitonin, D-dimer, fibrinogen, ferritin, and comorbidities including diabetes mellitus, hypertension, HIV, coronary disease, and renal disease, were associated with the severity of COVID-19.